Acquirers' Cultural Background and the Use of Earnouts. (January 2021) - Ewelt-Knauer, Corinna; Gefken, Johannes; Knauer, Thorsten; Wiedemann, David
This study investigates the effects of culture on the design of merger and acquisition (M&A) contracts. Specifically, we empirically analyze how the acquirer's cultural background influences the contractual choice to implement an earnout. We operationalize the acquirer's cultural background by using Hofstede's country-level indices for individualism, power distance, uncertainty avoidance, masculinity, and long-term orientation. Using a comprehensive sample of 9, 669 M&As, we find that earnout use is significantly positively associated with the acquirer's masculinity level. Furthermore, we provide evidence that earnout use is significantly negatively associated with the acquirer's power distance and uncertainty avoidance scores. Our study contributes to the literature by demonstrating that, in addition to economic theories, cultural differences are important in understanding the heterogeneity of earnout use.